2021
DOI: 10.3389/fmicb.2021.685408
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria HN6 Induced the Change and Reorganization of Fusarium Microflora in the Rhizosphere of Banana Seedlings to Construct a Healthy Banana Microflora

Abstract: Streptomyces aureoverticillatus HN6 was isolated in our previous study and effectively controlled banana Fusarium wilt. We explored the role of HN6 in constructing a healthy rhizosphere microflora of banana seedlings. The method of antibiotic resistance was used to determine the colonization ability of HN6. The effect of HN6 on the rhizosphere microbial communities was assessed using culture-dependent and high-throughput sequencing. The effect of HN6 on the infection process of the pathogen was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…abundance in the rhizosphere has been reported following PGP Streptomyces spp. inoculation (Yang et al, 2021). Further, the introduction of Bacillus velezensis NJAU‐Z9 was reported to shift bacterial and fungal communities and increase yield (Zhang et al, 2019), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…abundance in the rhizosphere has been reported following PGP Streptomyces spp. inoculation (Yang et al, 2021). Further, the introduction of Bacillus velezensis NJAU‐Z9 was reported to shift bacterial and fungal communities and increase yield (Zhang et al, 2019), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our explanation that SynCom treatment can change fungal community structure to confer better 5a, path 1 and 2 → 9] assume that SynComm application impacts the plant growth [number of flowers, plant height and root length] and productivity [yield] independently of SynComm-induced variations in soil biotic and abiotic properties via direct effects, that is, increase in plant growth and nutrient uptake via phytohormones like IAA, P-solubilisation and ammonia production [Mukherjee et al, 2020;Pereg & McMillan, 2015;Tabassum et al, 2017;Zhang et al, 2019]. The indirect effects of SynCom infer that microbial strain application impacts the plant variables through the changes in soil nitrogen and phosphorus concentration [Figure 5a, pathway 3 → 4] or soil microbiological properties [bacterial and fungal diversity and community structure; Figure 5a, path 5 → 7 → 9; Mukherjee et al, 2020;Pereg & McMillan, 2015;Tabassum et al, 2017;Yang et al, 2021]. The indirect effects of cultivar in our study assumes that cultivars affect soil microbiological and chemical properties [10 and 11, respectively], as well as plant growth and productivity [path 12 and 13, respectively;Hedden & Sponsel, 2015;Mukherjee et al, 2020;Pereg & McMillan 2015;Tabassum et al, 2017;Wei et al, 2019;Zhang et al, 2019]).…”
Section: Effect Of Syncom Application On Rhizosphere Microbesmentioning
confidence: 99%
“…In the past few decades, many studies on the screening and identification of these bacteria have been reported. Moreover, there is a rich diversity of plant PGPR ( Gange and Gadhave, 2018 ; Yang et al, 2021 ). Many genera of PGPR have been identified, such as Bacillus, Brevibacillus, Pseudomonas, Agrobacterium, Burkholderia, Streptomyces , and Thiobacillu ( Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on antibiotic production by antagonistic microbes, such as Bacillus sp., Pseudomonas sp., and Streptomyces sp. ( Beneduzi et al, 2012 ; Ngalimat et al, 2021 ; Yang et al, 2021 ). Bacillus spp., produce spores, which may be used to develop an effective microbial biopesticide formulation in the form of a biocontrol agent (BCA).…”
Section: Introductionmentioning
confidence: 99%